Expression and functional analysis of a recombinant Aquaporin Z from Antarctic Pseudomonas sp. AMS3 - Balakrishnan, S.; Rahman, R. N. Z. R. A.; Noor, N. D. M.; Latip, W.; Ali, M. S. M. (John Wiley and Sons, 2024)
Aquaporin (AQP) is a water channel protein from the family of transmembrane proteins which facilitates the movement of water across the cell membrane. It is ubiquitous in nature, however the understanding of the water transport mechanism, especially for AQPs in microbes adapted to low temperatures, remains limited. AQP also has been recognized for its ability to be used for water filtration, but knowledge of the biochemical features necessary for its potential applications in industrial processes has been lacking. Therefore, this research was conducted to express, extract, solubilize, purify, and study the functional adaptations of the aquaporin Z family from Pseudomonas sp. AMS3 via molecular approaches. In this study, AqpZ1 AMS3 was successfully subcloned and expressed in E. coli BL21 (DE3) as a recombinant protein. The AqpZ1 AMS3 gene was expressed under optimized conditions and the best optimized condition for the AQP was in 0.5 mM IPTG incubated at 25°C for 20 h induction time. A zwitterionic mild detergent [(3-cholamidopropyl) dimethylammonio]-1-propanesulfonate was the suitable surfactant for the protein solubilization. The protein was then purified via affinity chromatography. Liposome and proteoliposome was reconstituted to determine the particle size using dynamic light scattering. This information obtained from this psychrophilic AQP identified provides new insights into the structural adaptation of this protein at low temperatures and could be useful for low temperature application and molecular engineering purposes in the future.